ON THE SHEAR VIBRATIONS OF PIEZOELECTRIC HALF-SPACE, IN THE CASE WHEN DIELECTRIC CONDUCTING LAYER ON THE BOUNDARY SURFACE IS FASTENED - Sargsyan, K. H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2004)
Shear vibrations of elastic piezoelectric half-space (piezoelectric of 6 mm class hexogonal symmetry) covered by a dielectric layer is studied. The vibrations in the media are induced due to the periodical force acting on the dielectric layer. Displacements, corresponding electrical potentials as well in vacuum, dielectric layer and piezoelectric half-space are obtained using Fourie’s transformations. An asimptotic formula is obtained for displacement amplitude of points on infinite distance, from the point on which the force acts, where the part of Lyav’s electroelastic waves are separated.
Keywords: elastic piezoelectric half-space; hexogonal symmetry; vibrations; Fourie’s transformations